Serum Vitamin D status is associated with increased blastocyst development rate in women undergoing IVF. Issue 6 (December 2020) - Walz, Nikita L.; Hinchliffe, Peter M.; Soares, Mario J.; Dhaliwal, Satvinder S.; Newsholme, Philip; Yovich, John L.; Keane, Kevin N.
Abstract: Research question: To determine the relationship between vitamin D (VitD) status and embryological, clinical pregnancy and live birth outcomes in women undergoing IVF. Design: Cross-sectional, observational study conducted at a university-affiliated private IVF clinic. A total of 287 women underwent 287 IVF cycles and received a fresh embryo transfer. Patients had their serum 25-hydroxyvitamin D2/D3 (VitD) determined on the day of oocyte retrieval, which was analysed in relation to blastocyst development rate, clinical pregnancy and live birth outcomes. Results: In stepwise, multivariable logistic regression models, increases in blastocyst development rate, number and quality, along with embryo cryopreservation and utilization rates were associated with women with a sufficient VitD status (≥20 ng/ml). For a single increase in the number of blastocysts generated per cycle or embryos cryopreserved per cycle, the likelihood for the patient to be VitD sufficient was increased by 32% (odds ratio [OR] 1.32, 95% confidence interval [CI] 1.10–1.58, P  = 0.002 and OR 1.33, 95% CI 1.10–1.60, P  = 0.004, respectively). Clinical pregnancy (40.7% versus 30.8%, P  = 0.086) and live birth rates (32.9% versus 25.8%, P  = 0.195) in the sufficient VitD group versus the insufficient group were not significantly different and VitD sufficiency was not significantly associated with these outcomes. Conclusion: A strong relationship was observed between blastocyst development and VitD sufficiency. However, there was no association between VitD and clinical pregnancy or live birth outcomes. Further larger studies are needed to investigate whether the observed effect on blastocyst development may have downstream implications on subsequent clinical pregnancy or live birth rates, and on a potential mechanism where sufficient VitD concentrations are linked to improved IVF outcomes.